Comunidades sinodais: a importância da sinodalidade para a consolidação das Comunidades Eclesiais Missionárias no Brasil = Synodal Communities: the importance of synodality for the consolidation of Missionary Ecclesial Communities in Brazil = Comunidades sinodales: la importancia de la sinodalidad para la consolidación de las Comunidades Eclesiales Misioneras en Brasil - Paiva, Vinícius da Silva (Teocomunicação, 2023)
This article deals with the panorama of Ecclesiastical Missionary Communities (CEMs) in Brazil, articulating it with the theme of synodality. The ecclesial vocation of Christianity is analyzed from the perspective of Heribert Mühlen’s "ecclesial we". Taking as a reference the General Guidelines for the Evangelizing Action of the Church in Brazil 2019-2023, we reflect on the analogy of "home" as a place of welcome and fraternal relationships. Due to the missionary nature of the Church, personalized evangelization centered on the human person is proposed. The dynamics of "giving oneself" as an ideal of coexistence and synodal synergy as a decisive factor for the maturity of ecclesial communities are addressed. The danger of clericalism and the importance of lay autonomy stand out. In the end, the Lucan narrative of the Visitation (Luke 1:39-56) is presented as a paradigm for the missionary departure of the Church.